Dinamika Prosedur Hukum Formil Pembentukan Peraturan Perundang-Undangan - Zaifa, Gilang Abi; Pasah, Marip; Permata, Virna Amalia Nur; Nurulhuda, Nada Syifa (TERAJU: Jurnal Syariah dan Hukum, 2024)
As a country governed by the rule of law, Indonesia is certainly not exempt from legal policy in the process of formulating legislation. The concept of legal policy refers to the policies and procedures that the government can employ to establish a legal system. Based on this, the problem formulation arises regarding the nature of the political aspects of legislation in the Job Creation Law (Undang-Undang Cipta Kerja) and the development and participation of the society in the creation of the Job Creation Law. The research method used is normative juridical, with a statute and conceptual approach. The results of the discussion show that the political aspects determine the objectives of what will be formulated in the legislation. In Indonesia, the formulation must be based on Pancasila, which serves as the fundamental norm of the state. The increasing critical and wise development of society must be taken into account to involve them in the formulation of legislation. The involvement of society aims to ensure that the resulting regulations will be beneficial for the people.